Development of a related party identification system in the notarial deed process using biometric scanners - Ogika, A Aru; Salam, Abdul (Trigin Publisher, 2023)
This research focuses on the implementation of an innovative system for identifying related parties in the notarial deed process by integrating biometric scanners. The traditional notarial deed process often faces challenges in accurately identifying and verifying the parties involved, leading to potential legal and security issues. To address this, our study proposes the development of a robust Related Party Identification System (RPIS) that leverages biometric technology for enhanced authentication. The RPIS employs state-of-the-art biometric scanners to capture and analyze unique physiological and behavioral characteristics, such as fingerprints or facial features, of individuals participating in the notarial deed process. Through a systematic approach, the system aims to improve the accuracy, efficiency, and security of party identification, mitigating the risk of fraud and unauthorized access. The research methodology involves the design and implementation of the RPIS prototype, followed by rigorous testing and validation in a simulated notarial deed environment. The study evaluates the system's performance in terms of speed, accuracy, and reliability, considering various scenarios and potential challenges encountered in real-world situations. The anticipated outcomes of this research include the development of a practical and effective RPIS framework that can be seamlessly integrated into existing notarial processes. The proposed system has the potential to enhance the overall integrity of notarial deeds by ensuring a reliable and secure identification mechanism for all related parties involved. This research contributes to the evolving landscape of legal technology, offering a viable solution to the contemporary challenges associated with party identification in notarial practices.